Characterising stormwater gross pollutants captured in catch basin inserts. - Alam, M.; Anwar, A.; Sarker, D.; Heitz, Anna; Rothleitner, C. (2017)
The accumulation of wash-off solid waste, termed gross pollutants (GPs), in drainage systems has become a major constraint for best management practices (BMPs) of stormwater. GPs should be captured at source before the material clogs the drainage network, seals the infiltration capacity of side entry pits or affects the aquatic life in receiving waters. BMPs intended to reduce stormwater pollutants include oil and grit separators, grassed swales, vegetated filter strips, retention ponds, and catch basin inserts (CBIs) are used to remove GP at the source and have no extra land use requirement because they are typically mounted within a catch basin (e.g. side entry pits; grate or gully pits). In this study, a new type of CBI, recently developed by Urban Stormwater Technologies (UST) was studied for its performance at a site in Gosnells, Western Australia. This new type of CBI can capture pollutants down to particle sizes of 150µm while retaining its shape and pollutant capturing capacity for at least 1year. Data on GP and associated water samples were collected during monthly servicing of CBIs for one year. The main component of GPs was found to be vegetation (93%): its accumulation showed a strong relationship (r(2)=0.9) with rainfall especially during the wet season. The average accumulation of total GP load for each CBI was 384kg/ha/yr (dry mass) with the GP moisture content ranging from 24 to 52.5%. Analysis of grain sizes of GPs captured in each CBI showed similar distributions in the different CBIs. The loading rate coefficient (K) calculated from runoff and GP load showed higher K-values for CBI located near trees. The UST developed CBI in this study showed higher potential to capture GPs down to 150µm in diameter than similar CBI devices described in previous studies.